2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-2.13026
|View full text |Cite
|
Sign up to set email alerts
|

Inducible dominant negative ErbB2 rat spermatogonial line for generation of transgenic rat model and dissecting ERBB2 tyrosine kinase mediated pathways

Abstract: Summary. Aim: The ERBB2 receptors tyrosine kinase, also known as HER2/Neu, play an essential role in early organism development and modulation of cell behavior in varieties of tissue in an adult organism. Our aim was the generation of transgenic rat spermatogonial line capable of inducible expression of a dominant negative form of the ERBB2 protein in vitro and the transgenic rat as an animal model for dissection of the ERBB2 mediated signaling in vitro and in vivo. Materials and Methods: Donor derived rat spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Reduced activity of TRN neurons may explain abnormal sleep function [ 45 ]. Erbb2 receptor tyrosine kinase plays a major role in early development and regulation of various cell behaviors [ 46 ]. It has been found that androgen receptor (Ar) in the main circadian clock of suprachiasmatic nucleus regulates the effect of light on male activity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced activity of TRN neurons may explain abnormal sleep function [ 45 ]. Erbb2 receptor tyrosine kinase plays a major role in early development and regulation of various cell behaviors [ 46 ]. It has been found that androgen receptor (Ar) in the main circadian clock of suprachiasmatic nucleus regulates the effect of light on male activity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%